ANALISIS NILAI TAMBAH DAGING BABI SEGAR MENJADI SE’I BABI SIAP SAJI (STUDI KASUS USAHA AGROINDUSTRI SE’I BABI DI BAUN) - Arsita Anis Tamu Ina; Maria Yasinta Luruk; Arnoldus Keban (Universitas Nusa Cendana, 2016)
The role of agro-industries to increase the value-added of the products through processing method is essentially important, including fast smoked pork. During July 2016, an analysis of the value-added products of smoked pork of agro-industry located in Baun-Kupang was undertaken to determine whether increasing the quality of pork through processing method would increase both the value-added of fast smoked pork and the income of the entrepreneur.Data was collected through observations of pork processing in the agro-industry site and interviews based on the prepared questionnaires. The data obtained were analyzed using value-added analysis following the method of Hayami (1987) and contribution revenue analysis following the method of Soekartawi (1995). Increasing the quality of pork through processing method increases the value-added as much as Rp.34.397/Kg was observed in the present study. In addition, the contribution of smoked pork to the total income of the owner is 74.02%, and that is greater than the other meat products. Thus, it can be concluded that increasing the quality ABSTRAK Peranan agroindustri dalam upaya mengolah bahan mentah menjadi produk olahan untuk meningkatkan nilai tambah sangatlah diperlukan. Salah satu upaya yang dilakukan untuk meningkatkan nilai tambah adalah pengolahan daging babi segar menjadi se’i. Suatu studi tentang nilai tambah produk se’i babi telah dilaksanakan selama bulan Juli 2016 di Agroindustri se’i babi di Baun. Tujuan penelitian ini adalah: mengetahui nilai tambah pengolahan daging babi segar menjadi se’i babi siap saji dan mengetahui kontribusi dari se’i babi terhadap pendapatan pelaku agroindustri se’i babi di Baun. Pengumpulan data dilakukan melalui observasi dan wawancara. Analisis data yang digunakan adalah analisis nilai tambah menurut Metode Hayami dan analisis kontribusi pendapatan. Hasil penelitian menunjukkan bahwa nilai tambah dari proses pengolahan daging segar menjadi se’i adalah sebesar Rp.34.397/Kg. Kontribusi usaha se’i terhadap total pendapatan agroindustri adalah sebesar 74,02% dan lebih besar dari pada produk lain. Dengan demikian dapat disimpulkan bahwa usaha agroindustri se’i babi Baun memberikan nilai tambah dan keuntungan bagi pelaku agroindustri.